Applications of Umbral Calculus Associated with p-Adic Invariant Integrals on Zp - Dae San Kim; Taekyun Kim (Abstract and Applied Analysis)
Recently, Dere and Simsek (2012) have studied the applications of umbral algebra to some special functions. In this paper, we investigate some properties of umbral calculus associated with p-adic invariant integrals on Zp. From our properties, we can also derive some interesting identities of Bernoulli polynomials.